2005
DOI: 10.2903/j.efsa.2005.209
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of the Scientific Panel on Dietetic products, nutrition and allergies [NDA] related to the Tolerable Upper Intake Level of Sodium

Abstract: SUMMARYSodium is an essential nutrient involved in fluid and electrolyte balance and is required for normal cellular function. Dietary deficiency of sodium is very uncommon due to the widespread occurrence of sodium in foods.Sodium is present in foods as a normal constituent at a low level. It is also added to foods, mainly as sodium chloride (commonly known as salt) during processing, cooking and immediately prior to consumption, but also in other forms, for example as sodium nitrate, sodium phosphate or sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…All of the major mineral elements did not exceed the tolerable upper intake level (UI) for the adults, which are for Ca, Mg and Zn Fe, 2500, 250, and 25 mg/kg, respectively. For K, Mn, Mn, and Fe, there is not evidence in the EU for tolerable upper intake levels [43][44][45]. Considering the consumption of 1.7 kg [46] in the EU, honey is not a risk food, even in terms of potentially toxic elements.…”
Section: Resultsmentioning
confidence: 99%
“…All of the major mineral elements did not exceed the tolerable upper intake level (UI) for the adults, which are for Ca, Mg and Zn Fe, 2500, 250, and 25 mg/kg, respectively. For K, Mn, Mn, and Fe, there is not evidence in the EU for tolerable upper intake levels [43][44][45]. Considering the consumption of 1.7 kg [46] in the EU, honey is not a risk food, even in terms of potentially toxic elements.…”
Section: Resultsmentioning
confidence: 99%
“…Among the strengths of our work is the use of a three-day dietary record. Although this questionnaire is not a good method for calculating total sodium intake (the gold standard is the 24-h urine collection [5]), it is used as an adequate direct assessment for estimating the dietary sources of sodium as indicated by WHO [49]. Dietary data from this questionnaire were detailed by parents and children and allowed the description of the sources of sodium in foods and beverages, which is difficult in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, in 2005, experts of the European Food Safety Authority (EFSA) Working Panel concluded that, although it was not possible to determine a tolerable level of sodium intake for the population, the excess intake of dietary sodium is associated with cardiovascular damage and a detrimental effect on health [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of the DAR including its revisions (Austria, 2018) and the peer review report, both documents are considered as background documents to this conclusion.…”
Section: Discussionmentioning
confidence: 99%